2010
DOI: 10.1093/scan/nsq027
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric frontal cortical activity and negative affective responses to ostracism

Abstract: Ostracism arouses negative affect. However, little is known about variables that influence the intensity of these negative affective responses. Two studies fill this void by incorporating work on approach- and withdrawal-related emotional states and their associated cortical activations. Study 1 found that following ostracism anger related directly to relative left frontal cortical activation. Study 2 used unilateral hand contractions to manipulate frontal cortical activity prior to an ostracizing event. Right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…Previous research has provided ample evidence that cortical activation asymmetries, in particular frontal activation asymmetries, are important markers for motivational processes and social behavior (e.g., Fox et al, 1995Fox et al, , 1996Harmon-Jones et al, 2004;Peterson et al, 2011;Sutton and Davidson, 1997). The present findings suggest that neurophysiological activation asymmetries are also related to early prosocial behaviors.…”
Section: Discussionsupporting
confidence: 64%
“…Previous research has provided ample evidence that cortical activation asymmetries, in particular frontal activation asymmetries, are important markers for motivational processes and social behavior (e.g., Fox et al, 1995Fox et al, , 1996Harmon-Jones et al, 2004;Peterson et al, 2011;Sutton and Davidson, 1997). The present findings suggest that neurophysiological activation asymmetries are also related to early prosocial behaviors.…”
Section: Discussionsupporting
confidence: 64%
“…The left prefrontal cortex has been found to be involved in approach motivational processes; the right prefrontal cortex has been found to be involved in withdrawal motivational processes. Several studies have found that despite anger's negative valence, it is also associated with relative left frontal cortical activation (Harmon‐Jones & Peterson, ; Harmon‐Jones, Peterson, & Harris, ; Peterson, Gravens, & Harmon‐Jones, ; Peterson, Shackman, & Harmon‐Jones, ), further suggesting that anger is associated with approach motivation (for a review, see Harmon‐Jones, Gable, & Peterson, ).…”
Section: Methodology Of Examining the Acoustic Startle Eyeblinkmentioning
confidence: 99%
“…This study supports the finding that increases in rLFA may play a causal role in aggression. A more recent follow-up study also found that rLFA was a partial mediator of the relationship between hand contractions and anger induced by an ostracism task (Peterson, Gravens, & Harmon-Jones, 2011). Another study examined rLFA as a mediator of the relationship between stress and aggression (Verona, Sadeh, & Curtin, 2009).…”
Section: Evidence Supporting Rlfa As Mediator Of Emotionmentioning
confidence: 97%